An Analytical Study of Electoral Reforms and Role of Election Commission in Indian Democracy - Dr. Rohitas Meena; Sujeet Kumar Jha (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Elections are the cornerstone of any democratic system, enabling citizens to choose their representatives and hold them accountable. As the world’s largest democracy, India presents a unique electoral landscape shaped by its vast population, complex social structure, and the most extensive written constitution globally. The Election Commission of India (ECI), an autonomous constitutional authority, is entrusted with administering, supervising, and conducting free and fair elections at both the state and national levels. This paper explores the evolving nature of electoral reforms in India and the critical role of the Election Commission in safeguarding democratic values. It examines the influence of the Indian Supreme Court in shaping electoral laws, particularly concerning criminalization in politics, the introduction of NOTA, and the enforcement of the Model Code of Conduct. Through a review of literature and a discussion on electoral mechanisms, this study highlights how reforms, technology adoption, and legal interventions contribute to enhancing transparency, accountability, and participation in the electoral process. Ultimately, the findings underline the importance of continuous reform and judicial oversight to strengthen India’s democratic framework.